Tactics of Altered Consumption: Young People’s Drinking Choices in the Italian Movida - Beccaria, Franca; Rolando, Sara; Petrilli, Enrico; Arcieri, Luigi (Italian Sociological Review, 2022)
Urban nightlife is often depicted as a homogeneous category dominated by the entertainment industry and characterised by at risk drinking practices. Taking on a more critical perspective, which recognises the heterogeneity of the physical and social settings as well as how nightgoers exercise their agency to manipulate and shape products and spaces defined by the consumeristic economic order, the paper aims to 1) explore the physical and social settings of two districts of Torino (North Italy) characterised by an intense nightlife, and 2) understand young people’s tactics with regard to alcohol consumption. The study adopted a mixed-methods approach including non-participant observation (40 hours) and face-to-face interviews (No. 22). Results show that youth drinking in an urban nightlife setting is a ‘tactical operation’ that concerns both the choice of what, how and where to consume and how to reduce potential risks. Indeed, young people embrace the possibilities offered by the night districts to achieve their goals (mainly to socialize and have fun) while limiting negative outcomes by adopting self-regulation and harm reduction practices.